Hygiene and Health using combination of Tea and Soap among Malaysians into Invention of new Aromatherapy Tea Soap Packaging - Abu Samah, Ahmad Lotfi; Santhanasamy, Joshua Edwin; Abd Rahman, Nazariah; Zhanglu, Zhanglu (Environment-Behaviour Proceedings Journal, 2023)
This study explored the need for a new soap and its aromatherapy benefit from branding soap and branding tea among Malaysians. It also examined the importance of aromatherapy benefiting soap for consumers. This project is based on a survey of respondents all from the Selangor and Klang Valley area, both male and female from various ages. Results shared by respondents suggested that the need for aromatherapy benefits in soap and new fragrances is high among consumers. Furthermore, the outcome of this study shows that many respondents indicated that a combination of tea and aromatherapy soap helps them to reduce their stress and anxiety.